THE ROLE OF INFORMATION TECHNOLOGY IN IMPROVING THE QUALITY OF HEALTH SERVICES IN HOSPITALS - Inacio Sarmento Viegas (Al-Makki Publisher, 2024)
This study aims to identify, analyze, and provide recommendations for the effective implementation of information technology to improve the quality of health services in hospitals as well as to find out how the IT process has become an integral component in various sectors, including business, education, government, and health. The methodology used in this study is a literature study and secondary data analysis as well as interviews with health practitioners and information technology experts with a review of scientific articles, research reports, and other publications, data from the Ministry of Health, and relevant national surveys. This will help in identifying current trends, challenges, and opportunities in the application of information technology in hospitals. Information technology has a positive impact on the quality of health services through operational efficiency, accuracy and security of patient data, increased patient satisfaction, and improved accessibility of services. There are challenges and barriers in the implementation of information technology such as implementation costs, training and human resources, data security and privacy, and resistance to change. The implementation of information technology in hospitals has great potential to improve the quality of healthcare services. However, challenges and barriers such as implementation costs, training needs, data security, and resistance to change must be overcome to achieve success.